LIFE REVIEW THERAPY FOR OLDER ADULTS WITH DEPRESSIVE SYMPTOMS IN GENERAL PRACTICE: RESULTS OF A PILOT EVALUATION. (16th November 2018) - Prins, M; Hendriks, L; Veenendaal, L; Veerbeek, M; Willemse, B
Abstract: Objective: Depression is a common health problem in older adults. General practices play an important role in detecting and treating depressive symptoms in older adults. However, evidence-based psychosocial interventions for general practices to prevent depressive symptoms from developing into a major depressive disorder are lacking. Therefore, an adapted version of the indicated preventive life review therapy group intervention called Looking for Meaning (LFM) was developed for general practice and a pilot evaluation was conducted. LFM proved effective in various settings, including specialized mental health care. Methods: A pretest-posttest design was used. In six general practices the adapted intervention was given, with 5–7 participants per group. One week before and one week after the intervention participants completed questionnaires about depressive and anxiety symptoms, psychological well-being and mastery. The posttest questionnaire also included an evaluation of the intervention. Results: Twenty-nine participants completed the pretest and posttest. Most participants were satisfied with the adaptations of the number and length of the sessions. The overall sample showed a significant decrease in depressive symptoms after the intervention. A trend was found for the improvement of psychological well-being. No impact was found on anxiety symptoms and mastery. The improvement on depressive symptoms of participants with clinically relevant depressive symptoms at baseline was significantly greater compared to the overall sample. Conclusion: The intervention is feasible and acceptable for older adults with depressive symptoms and affects their depressive symptoms positively. Therefore, LFM can be recommended as a preventive intervention for depressive symptoms in general practice.